Transient Power Quality Performance of Multi Photovoltaics using MPPT P and O/MPPT Fuzzy - Amirullah Amirullah; Agus Kiswantono; Ontoseno Penangsang; Adi Soeprijanto (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper presents comparative performance of transient power quality due to multi photovoltaic (PV) integration to grid at both fixed temperature and solar irradiation connected using Maximum Power Point Tracking Perturb and Observe (MPPT P and O)/MPPT Fuzzy. This research is performed as five transient of short-circuit faults on point common coupling (PCC) bus. An artificial intelligence with fuzzy logic controller (FLC) is used to set duty cycle with step variable to control DC/DC boost converter, generate quick convergence to determine MPPT for controlling of PV output voltage. Furthermore the result is compared with MPPT P and O. During transient phase, non-symmetrical faults are able to result an unbalance current/voltage greater than symmetrical faults. On symmetrical faults, MPPT Fuzzy is able to resultan average THD voltage/THD current smaller than MPPT P and O. Otherwise on non-symmetrical faults, MPPT P and O is able to resultan average THD voltage/THD current slightly smaller than MPPT Fuzzy. Both of MPPT P and O and MPPT Fuzzy on all short circuit faults during transient phase are able to result significantly smaller current average THD current than average THD voltage and limits of THD prescribed in IEEE 519. This research is simulated using Matlab/Simulink environment.